A public banking option as a mode of regulation for household financial services in the US. Issue 4 (1st October 2020) - Herndon, Thomas; Paul, Mark
Abstract: The current financial system fails to adequately serve millions of consumers, resulting in widespread financial exclusion and consumer financial protections abuses. To address these problems, this paper proposes a public option in household financial services. A public option as a mode of regulation is defined as the government using the direct provision of services to households and intermediaries as a tool to regulate in the public interest. The public option explored would include two components. First, the federal government would create a public bank that directly provides households with basic transaction services and consumer credit. Second, the public bank would directly provide intermediaries with a service, through managing an online financial services marketplace where public products would compete alongside private products. A public option of this type would create the financial infrastructure required for universal service, as well as prevent consumer financial protection abuses through public-private competition.